2009
DOI: 10.1149/1.3194800
|View full text |Cite
|
Sign up to set email alerts
|

Ternary PtRuNi Nanocatalysts Supported on N-Doped Carbon Nanotubes: Deposition Process, Material Characterization, and Electrochemistry

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Ternary PtRuNi nanocatalysts supported on N-doped carbon nanotubes: deposition process, materials characterization, and electrochemistry Sun, C-L.; Hsu, Y-K.; Lin, Y-G.; Chen, K-H.; Bock, C.; MacDougall, Barry; Wuy, X.; Chen, L-C.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…particle size 3-4.5 nm, 2.6 higher MOR current compared to PtRu [487] Pt-SnO2 NCNTs ALD of SnO2 on NCNTs grown directly on carbon paper SnO2 around 1.5 nm, Pt NPs 1.5-4 nm. 125 times improved ORR and MOR activities [493] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…particle size 3-4.5 nm, 2.6 higher MOR current compared to PtRu [487] Pt-SnO2 NCNTs ALD of SnO2 on NCNTs grown directly on carbon paper SnO2 around 1.5 nm, Pt NPs 1.5-4 nm. 125 times improved ORR and MOR activities [493] …”
Section: Discussionmentioning
confidence: 99%
“…[694], PtRu deposited on carbonized ionic polymer-modified CNTs [482] and Rudecorated Pt/MWNCNTs prepared by atomic layer deposition [483]. Ternary PtRuNi catalyst deposited over NCNTs provided further improvement of MOR activity by a factor of 2.6, compared to binary PtRu catalyst [487].…”
Section: Low-molecular Weight Alcohol Oxidation and Related Fuel Cellmentioning
confidence: 99%
“…The experiment [31] found that the methanol oxidation current of the ternary Pt-Ru-Ni catalyst increased by as much as a factor of 2.6 in comparison with that of the binary PtRu catalyst. This can contribute to the controlled synthesis and understanding of fuel-cell catalysts [31]. Furthermore, the high efficiency of Ag nanoparticles deposited over activated carbon has been demonstrated in controlling microorganisms in water [32].…”
Section: Introductionmentioning
confidence: 97%
“…For example, the catalytic activity of the Au-Ag-Pd trimetallic nanoparticles was investigated and found to be efficient in catalyzing the Heck reaction [30]. The experiment [31] found that the methanol oxidation current of the ternary Pt-Ru-Ni catalyst increased by as much as a factor of 2.6 in comparison with that of the binary PtRu catalyst. This can contribute to the controlled synthesis and understanding of fuel-cell catalysts [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the design of a composite electrode, it is ideal to fabricate an extremely thin layer (∼nm) of nanostructured MnO 2 onto the current collector, controlling the coating layer thickness and uniform surface coverage to reach the high theoretical specific capacitance. To achieve this goal, the direct-growing nitrogen-incorporated carbon nanotubes (CNxNTs) on the carbon cloth (CC) function as a hierarchical current collector, which is used to improve electronic conductivity and increase specific surface area [21,22]. Due to the incorporation of nitrogen, CNxNTs also inherently possess surface defects, creating a further increase of anchoring sites for uniform deposition of MnO 2 nanostructure, and facilitating the charge-transfer between active materials and CNxNTs.…”
Section: Introductionmentioning
confidence: 99%